Development of Electronic Module with Project based Learning - Fadhilah, Nurul; Thahir, Rahmatia (BIOEDUSCIENCE, 2023)
Background: Educators in the 21st century are faced with the demand to integrate technology into the learning process. One example is by using an electronic module (e-module). The electronic module is an innovative learning media presented digitally, including text, images, and video. This study aims to develop a valid and practical e-module based on project-based learning. Methods: The research and development (R&D) method was used in this study by adopting the Alessi & Trollip development model. Alessi & Trollip's model has three stages: planning, design, and development. Results: The results of e-module validation based on content experts show a value of 4.39 with a very valid category, and the percentage of validator assessment is 87.71%, which means that e-module is in the very feasible category. The media expert validator's assessment was 4.48, which means it is in the very valid category. The presentation of the validator's assessment was 89.58%, meaning that the e-module is suitable for use in the learning process. Student response to e-module based on project-based learning was 4.35 and categorized as very good. The percentage of student interest in the e-module is 86.90%. This value indicates that the e-module based on project-based learning meets the criteria of practicality and is feasible for students to use in the learning process. Conclusions: The e-module based on project-based learning developed in this study shows valid validity and practicality, So the e-module is appropriate for use in the learning process. The use of e-modules based on project-based learning also has the potential to increase students' critical thinking skills.